Las opiniones consultivas de la Corte Interamericana en el control de convencionalidad - Sagüés, Néstor Pedro (2015)
This article discusses the conventionality control according to the jurisprudence of the interamerican Court of Human rights. Particularly, the author analyzes whether advisory opinions, like judgments, constitute the “controlling material” of the conventionality control. in this way, the author presents and discusses theses derived from the referred jurisprudence, to conclude that the interpretative guidelines contained in advisory opinions of the interamerican Court of Human rights constitute the “controlling material” under certain circumstances.